The appropriate collection and presentation on building surveying data / Muhammad Husnir Rahman Mohd Hapiz - Mohd Hapiz, Muhammad Husnir Rahman (Faculty of Architecture, Planning and Surveying, 2015)
This study determines the appropriate collection and presentation on building surveying data. The researcher had narrow research area on company at Selangor state only. Company that the researcher approaches are SGS (Malaysia) Sdn. Bhd. and JKR Selangor. The researcher make interview with building surveyor at the company and distribute questionnaire to the specific individual. The researcher wants to know the prior basic details of the property before surveying work. The researcher concluded that all the respondent agree with scope of instruction, client name, address/location, date, description/type, type, accommodation, size, current use, road and access, tenure, fire certificate and certificate of lease. Also, the researcher wants to investigate the method to gather data and information by building surveyor. The researcher concluded that all the respondents agree with visit to site, initial researcher, property owner, solicitor, local authority and other parties. Also, the researchers concluded that all respondents agree that the present tense should be used for all matters of description in reports and the past tense should be used for all comments on condition; direct on-site dictation method; about to be included approximate building costs in reports; about to be included disclaimer of liability or exclusion clauses and the professional indemnity insurers in a report; important to set out clearly in the report what the client should to do; about it is common for surveyor subsequent dealings (discuss the report) with clients after the report been submitted; about it is prior to have a complaints handling procedure in place with the report; about it is particular to have a good report with excellent grammar and spelling; necessary to report on the design and construction, condition, cause of defects and remedial work required From the questionnaire, there are several recommendations stated from the respondents. The recommendations are to suggest the appropriate collection and presentation on building surveying data.